Imaging of Renal Transplant Complications throughout the Life of the Allograft: Comprehensive Multimodality Review - Sugi, Mark D; Joshi, Gayatri; Maddu, Kiran K; Dahiya, Nirvikar; Menias, Christine O (Radiographics, 2019)
The kidney is the most commonly transplanted solid organ. Advances in surgical techniques, immunosuppression regimens, surveillance imaging, and histopathologic diagnosis of rejection have allowed prolonged graft survival times. However, the demand for kidneys continues to outgrow the available supply, and there are efforts to increase use of donor kidneys with moderate- or high-risk profiles. This highlights the importance of evaluating the renal transplant patient in the context of both donor and recipient risk factors. Radiologists play an integral role within the multidisciplinary team in care of the transplant patient at every stage of the transplant process. In the immediate postoperative period, duplex US is the modality of choice for evaluating the renal allograft. It is useful for establishing a baseline examination for comparison at future surveillance imaging. In the setting of allograft dysfunction, advanced imaging techniques including MRI or contrast-enhanced US may be useful for providing a more specific diagnosis and excluding nonrejection causes of renal dysfunction. When a pathologic diagnosis is deemed necessary to guide therapy, US-guided biopsy is a relatively low-risk, safe procedure. The range of complications of renal transplantation can be organized temporally in relation to the time since surgery and/or according to disease categories, including immunologic (rejection), surgical or iatrogenic, vascular, urinary, infectious, and neoplastic complications. The unique heterotopic location of the renal allograft in the iliac fossa predisposes it to a specific set of complications. As imaging features of infection or malignancy may be nonspecific, awareness of the patient's risk profile and time since transplantation can be used to assign the probability of a certain diagnosis and thus guide more specific diagnostic workup. It is critical to understand variations in vascular anatomy, surgical technique, and independent donor and recipient risk factors to make an accurate diagnosis and initiate appropriate treatment. RSNA, 2019.